A comparative study of the readability of secondary science textbooks - Espartero, Angeles Cabrillos (1976)
This study is an attempt to compare the readability of twelve secondary science textbooks, six of which were developed by the U.P. Science Education Center and the other six corresponding in grade level to the first six, but done by other authors. The main instrument used in this study is the Flesch Readability Formula. The writer suggested that any attempt to identify the criteria to be utilized by educators in such selection will be a positive contribution to education.